Transformasi Pondok Pesantren Dar Al-Maarif Basilam Baru Kabupaten Labuhanbatu Selatan Tahun 1992-2021 - Nasution, Hotmaidah; Riza, Faisal; Faturrahman, Muslih (Asian Journal of Islamic Studies and Da'wah, 2024)
This research aims to determine the transformation of the Dar Al-Maarif Basilam Baru Islamic boarding school. The research used is a historical research method through heuristic stages of collecting historical sources by means of interviews and archives in the form of Islamic boarding school founding deeds, verification (criticism of data), interpretation and historiography. In this research, the author uses a historical approach. As for the theory, the author uses Aguste Comte's social theory. The aim of this research is to find out the history of the establishment of the Dar Al-Maarif Basilam Baru Islamic Boarding School, South Labuhanbatu Regency in 1992-2021 and the development of the Dar Al-Maarif Basilam Baru Islamic Boarding School in 1992-2021. The results of this research concluded that the New Dar Al-Maarif Basilam Islamic Boarding School was founded in 1992 by Sheikh Abdullah Efendi. Before the establishment of the Dar Al-Maarif Basilam Baru Islamic Boarding School, it was only a religious pilgrimage and study carried out for the people of Sosopan village and its surroundings. The Dar Al-Maarif Basilam Baru Islamic Boarding School has developed from various aspects which include the development of facilities and infrastructure, the development of students, the development of work programs. Developments in terms of prayer rooms used for student activities. The development of santri students, which was initially only dozens of santri, has now reached a thousand santri. Dar Al-Maarif Islamic Boarding School has progressed in its development due to several factors that influence it, namely the role of the founder of the Islamic boarding school, family, support from the surrounding community and the infrastructure it has. Meanwhile, the inhibiting factors are the behavior of the students, management cadre formation, and the Islamic boarding school's financial resources.